Engaging with Islamic Narratives in a Digital Space: Insights from High School Readers - Khadijah; Andi Anto Patak; Fitriyani (INTERACTION: Jurnal Pendidikan Bahasa, 2025)
This study aims to examine how high school students perceive Islamic narrative texts presented through a digital reading platform, focusing on clarity, relevance, and spiritual value. It explores how students engage with these texts as digital technology increasingly becomes a part of religious education. The research was conducted at an Islamic senior high school and focused on how students interpret the clarity, relevance, and spiritual value of Islamic texts delivered in English. Using a qualitative descriptive method, data were collected through Focus Group Interviews (FGIs) with ten students who were active users of the SMART READING virtual platform. Thematic analysis revealed that students generally perceived the content positively. They found the stories about prophets to be morally enriching and relatable to their daily lives, with values such as honesty, patience, and gratitude standing out. However, suggestions were made to improve the variety of content, include visual support, and add interactive features such as quizzes and vocabulary aids. This study contributes to digital religious education by emphasizing the importance of relevant, engaging, and spiritually meaningful content in supporting student learning and moral reflection.